Greece : Request for Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Greece. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Greece's Request for Stand-By Arrangement (SBA). The program will be narrowly focused on policies that can help restore macroeconomic stability in the medium run and facilitate market access in Greece. It seeks to provide breathing space to mobilize broad political support for the deeper structural reforms needed for Greece to liberalize its economy and prosper within the euro area in the long term. The program will also provide a framework for Greece's European partners to deliver debt relief to restore Greece's debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet